(untitled) (CAHIERS MAGELLANES-NS, 2024)
Probiotics are defined as “live microorganisms that, when administered in adequate amounts, confer a health benefit on the host” [1]. To date, probiotics have been known by most people for its benefits on the gastro-intestinal systems. Studies have shown that probiotics help in controlling intestinal infections, relieving constipation and diarrhoea as well as improving lactose intolerance [2]. Research has also been done to suggest that probiotics are useful in preventing oral diseases such as dental caries, periodontal infections, and halitosis [3–5]. Following are examples of research that showcased the benefits of probiotics against oral diseases. Näse et al. [6] demonstrated a significant decrease in dental caries and a lowered S. mutans count in the saliva of patients, after consuming dairy products containing L. rhamnosus for seven months. Other than that, in a study done by Krasse et al. [7], there was significant reduction of plaque index in patients with gingivitis, after two weeks of taking chewing gums containing L. reuteri. On the other hand, probiotics also showed effectiveness in treating halitosis. When anaerobic bacteria like Fusobacterium nucleatum, P. gingivitis, P. intermedia, and T. denticola degrade food proteins, they produce volatile sulphur compounds (VSC), which are responsible for the unpleasant odour. Kang et al. [8] suggested that Weisella cibaria produces hydrogen peroxide which can inhibit the growth of F. nucleatum. Various studies have been conducted to assess the knowledge, attitude, and practice of probiotics in various groups of population. A questionnaire study by Rahmah et al. [9] showed that more than half health science students in a university in Indonesia had fair knowledge, positive attitude, and positive practice towards probiotics. In Lebanon, Hashem Taleb et al. [10] found that 51.6% of paediatricians have a good knowledge about probiotics. Krishnan et al. [11] reported that even though majority of dental students of Chennai city knew about probiotics along with its uses, only 19% had applied the knowledge into practice. In Puducherry, Santhanam et al. [12] revealed that dental practitioners had knowledge level towards probiotics that was well above acceptable level. In Ghaziabad, Muchhal et al. [13] found that majority of dental students were aware about probiotics and its health benefits. Poorni et al. [14], revealed that there was good basic knowledge, attitude, and practice towards probiotics among the Indian population. Studies have shown potential benefits of probiotics that help in preventing and treating systemic and oral conditions. Research regarding the knowledge, attitude, and practice towards probiotics have been carried out in the healthcare sector, including the dental field. Inspired by the interest in the field of Dentistry, we have chosen to assess the knowledge, attitude, and practice towards probiotics among the dental students of our institution. Our study aims to contribute to understanding the role of probiotics in healthcare and to inform about the development of evidence-based approaches to dental healthcare among dental students of MUCM.